Damage initiation in brittle and ductile materials as revealed from a fractoluminescence study - Alexandre Chmel; Igor’ Shcherbakov (Fracture and Structural Integrity)
A set of heterogeneous and homogeneous materials differing in their brittle and ductile characteristics (granite, marble, silica ceramics, silicon carbide, organic glass) were subjected to impact damaging by a falling weight. Multiple chemical bond ruptures produced by elastic waves propagating from a damaged zone were accompanied by the photon emission generated throughout the sample (tribo- or fractoluminescence, FL). The statistical analysis of the FL time series detected with high resolution (10 ns) showed that the energy release distributions in brittle solids follow the power law typical for the correlated nucleation of primary defects. At the same time, the formation of damaged sites in ductile materials (marble and organic glass) was found to be fully random.